Innovative strategies minimize engraftment syndrome in multiple myeloma patients with novel induction therapy following autologous hematopoietic stem cell transplantation. (December 2018) - Gutiérrez-García, Gonzalo; Rovira, Montserrat; Magnano, Laura; Rosiñol, Laura; Bataller, Alex; Suárez-Lledó, María; Cibeira, María; Larrea, Carlos; Garrote, Marta; Jorge, Sofia; Moreno, Ana; Rodríguez-Lobato, Luis; et al.
Abstract Autologous stem cell transplantation (PBSCT) is standard for young patients in MM and its TRM has decreased after the 2000s. Bortezomib and immunomodulatory agents (IMiDs) in MM have improved the outcome. However, they seem to boost pro-inflammatory stage increasing the incidence of engraftment syndrome (ES). Favorable factors in PBSCT such as G-CSF could increase inflammatory stage during transplant. Corticosteroids have shown an excellent response of ES and some authors propose them as prophylaxis for ES. The aim was to analyze the impact of G-CSF avoidance and corticosteroids' prophylaxis in 170 patients diagnosed of MM treated with bortezomib/IMiDs that underwent PBSCT. We established three groups: Group-I [(G-CSF_administration), 60 patients (35%)], group-II [(nonG-CSF), 60 patients (35%)] and group-III [(nonG-CSF plus corticosteroid's prophylaxis), 50 patients (30%)]. A decreased ES incidence among groups was observed: 62, 42, and 22% (P  < 0.0001). The incidence of symptoms mimicking a capillary leak syndrome associated with ES dropped: 43, 32, and 0% (P  = 0.03). The G-CSF avoidance and corticosteroids had impact over admission 24, 21, and 20 days (P  = 0.001). The most important variables related to ES were HCT-CI >2 (p  < 0.0001; HR 8.5) and risk groups (p  < 0.0001; HR 7.2). Hence, G-CSF avoidance and corticosteroid's prophylaxis decrease morbidity in patients undergoing PBSCT with MM treated with bortezomib/IMiDs.